Customizable 3D printed perfusion bioreactor for the engineering of stem cell microenvironments - Dupard, Steven J.; Garcia, Alejandro Garcia; Bourgine, Paul E. (Frontiers in Bioengineering and Biotechnology, 2023)
Faithful modeling of tissues and organs requires the development of systems reflecting their dynamic 3D cellular architecture and organization. Current technologies suffer from a lack of design flexibility and complex prototyping, preventing their broad adoption by the scientific community. To make 3D cell culture more available and adaptable we here describe the use of the fused-deposition modeling (FDM) technology to rapid-prototype 3D printed perfusion bioreactors. Our 3D printed bioreactors are made of polylactic acid (PLA) resulting in reusable systems customizable in size and shape. Following design confirmation, our bioreactors were biologically validated for the culture of human mesenchymal stromal cells under perfusion for up to two weeks on collagen scaffolds. Microenvironments of various size/volume (6 to 12 mm in diameter) could be engineered, by modulating the 3D printed bioreactor design. Metabolic assay and confocal microscopy confirmed the homogenous mesenchymal cell distribution throughout the material pores. The resulting human microenvironments were further exploited for the maintenance of human hematopoietic stem cells. Following 1 week of stromal coculture, we report the recapitulation of 3D interactions between the mesenchymal and hematopoietic fractions, associated with a phenotypic expansion of the blood stem cell populations. Our data confirm that perfusion bioreactors fit for cell culture can be generated using a 3D printing technology and exploited for the 3D modeling of complex stem cell systems. Our approach opens the gates for a more faithful investigation of cellular processes in relation to a dynamic 3D microenvironment.